IZIN POLIGAMI KARENA DORONGAN ISTERI: STUDI PUTUSAN NO. 790/PDT.G/2013/PA. SMN - Khoiruddin, Isro (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Indonesia is a nation in which the majority of its fellow citizens adhere to Islam. This furthermore stands as one of the reasons in creating judicial institution that specifically deals with Muslim judicial matters. Poligamy permit is an example of judicial matters subsumed under the jurisdiction of Religious [Islamic] Court. Despite of the fact that Islam recognizes polygamy, the intended person has to file polygamy permit to Islamic court for the sake of administrative order due to monogamy principle practiced within marital affairs. The Islamic court has the authority to look into the subjects involved in order to determine whether it is reasonable to grant the petition or not. This is however deployed to anticipate discrimination, right and responsibility abuses, and to reach verdicts that represent justice, utility, and legal certainty.